Zingiberaceae endémicas del Perú - León, Blanca (2006)
The Zingiberaceae family are represented in Peru with three genera and 19 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), all herbaceous plants. Here we recognize one endemic species, occurring in the lower limits of the Humid Premontane Forest region, between 700 and 800 m elevation. The species has not yet been reported from within a protected area.